PENGARUH KEPEMIMPINAN DAN TEAM WORK TERHADAP KINERJA KARYAWAN DI KOPERASI SEKJEN KEMDIKBUD SENAYAN JAKARTA - Marpaung, Marudut (Lembaga Layanan Pendidikan Tinggi Wilayah III Jakarta, 2014)
Cooporation is borrow-store activity and it to represent any economy sector very importing in Indonesia, sucessfully or no cooperation is ledearship, teamwork and staff performannce with in particular in Sekjen Kemdikbud Senayan Jakarta. This problem, what is positif or negatif effect of ledearship, teamwork for staff performannce of cooperation in Sekjen Kemdikbud Senayan Jakarta. research of aim is to know ledearship and teamwork effect significant for staff performannce of cooporation in Sekjen Kemdikbud Senayan Jakarta, it will have been hope from research to give function of staff teamwork in Sekjen Kemdikbud Senayan Jakarta. Therefore research of method with needed is descriptif cuantitatif research. Research data is reabilility, 0,829 > 0,378. Research result of partial variable is significant because ledearship to staff performance th (2,380) > t t (1,725) and teamwork to staff performance is th (3,170) > t t (1,725) therefore Ho leaved and Ha gived. And then F test for ledearship variable and teamwork variable simultant to performance variable F h (8,577) > F t (3,592), therefore Ho leaved and Ha gived. And determinat value is r2 = 0,709 = 50,2%. Finally, to point out is ledearship and teamwork simultant to give contribution is good enough (50,2%) to staff performance in Sekjen Kemdikbud Senayan Jakarta.